2021
DOI: 10.2478/rput-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Bioleaching Experiment of E-Waste

Abstract: Nowadays, we can hardly imagine our life without the achievements of modern technology, such as refrigerators, televisions, computers, or smartphones. Producers are pushing consumers to buy newer, more modern appliances instead of repairing the original ones. However, all the devices represent a huge amount of waste. E-waste is one of the fastest growing types of waste, and only less than a half of it is recycled. Its disposal poses a great challenge for the population and constitutes a huge burden for the env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…However, a significant decrease was witnessed with a PS of 500-700 µm where an ORP of 400 mV on the last day of the experiment occurred, from an ORP of 720 mV. These findings are not peculiar to this study as they were also witnessed by other authors [4,25]. These findings demonstrated that the PS has an impact on microbial activity.…”
Section: Physicochemical Conditions During the Bioleaching Processsupporting
confidence: 78%
See 4 more Smart Citations
“…However, a significant decrease was witnessed with a PS of 500-700 µm where an ORP of 400 mV on the last day of the experiment occurred, from an ORP of 720 mV. These findings are not peculiar to this study as they were also witnessed by other authors [4,25]. These findings demonstrated that the PS has an impact on microbial activity.…”
Section: Physicochemical Conditions During the Bioleaching Processsupporting
confidence: 78%
“…The pH of the medium was corrected, when necessary, by adding droplets of 98 v/v% H 2 SO 4 to reduce the alkalinity and the formation of jarosite participates that is caused by a pH above 2 [26]. This increase in pH was also observed in various studies [2,4,27]. The ORP profile also showed a decrease when the e-waste was added, and this decrease varied depending on the PS.…”
Section: Physicochemical Conditions During the Bioleaching Processmentioning
confidence: 73%
See 3 more Smart Citations